1985
DOI: 10.1056/nejm198506133122406
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Correlates of Survival in Advanced Malignant Disease?

Abstract: Prospective studies of the general population have isolated specific social and psychological factors as independent predictors of longevity. This study assesses the ability of these factors, plus two others said to influence survival in patients with cancer, to predict survival and the time to relapse after a diagnosis of cancer. Patients with unresectable cancers (n = 204) were followed to determine the length of survival. Patients with Stage I or II melanoma or Stage II breast cancer (n = 155) were followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
0
7

Year Published

1988
1988
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(131 citation statements)
references
References 14 publications
8
116
0
7
Order By: Relevance
“…In some of these studies, HR QL was found to be even more predictive of survival than known biologic prognostic factors (36, 40 -43). It should be noted, however, that in a few other studies no signi cant relationship was found between H R QL and time to death (45,46). There is some dispute about the explanation of these contradictory ndings.…”
Section: To Predict Mortalitymentioning
confidence: 88%
“…In some of these studies, HR QL was found to be even more predictive of survival than known biologic prognostic factors (36, 40 -43). It should be noted, however, that in a few other studies no signi cant relationship was found between H R QL and time to death (45,46). There is some dispute about the explanation of these contradictory ndings.…”
Section: To Predict Mortalitymentioning
confidence: 88%
“…12 Popular literature about exceptional recoveries, for example, books such as Bernie Siegel's 1 popular Love, Medicine and Miracles and Carl Simonton's 15 Getting Well Again propose a potential link between psychosocial variables and prolonged survival, a relationship that has also been investigated in the scientific literature. 16,17 Conclusions from research investigating the role of psychosocial variables in survival are inconsistent. In the mid-1980s, Cassileth et al stated that "the inherent biology of the disease alone determines the prognosis, overriding the potentially mitigating influence of psychosocial factors," 16(p1555) whereas Berland argued 10 years later that there is "growing consensus" that "biological (that is, immunological) functions cannot be separated from psychological factors."…”
mentioning
confidence: 99%
“…This could also lead to a decrease in emotional burden (Bradley et al 2007) as by having the awake craniotomy patients may not suffer many of the psychosocial effects reported in brain tumour research (Armstrong, 2004;Bradley et al 2007;Cassileth, Lusk, Miller, Brown, & Miller, 1985;Khalili, 2007).…”
Section: Quality Of Life For Brain Tumour Patientsmentioning
confidence: 99%